Trocar Configuration in laparoscopic hysterectomy for benign indications - Georgios Grigoriadis; Androniks Mumdzjans (Wolters Kluwer Medknow Publications, 2021)
Hysterectomy is the most common gynecological surgical procedure worldwide. In recent years, there has been a significant increase in the proportion of hysterectomies performed laparoscopically. Despite attempts to standardize the procedure, there are various approaches available to the surgeon, in terms of number and position of laparoscopic trocars. We have conducted an electronic search on PubMed and, in this article, we present different laparoscopic trocar configurations in order to perform a laparoscopic hysterectomy